2022
DOI: 10.1186/s12978-022-01447-1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting respectful maternity care using a behavioral design approach in Zambia: results from a mixed-methods evaluation

Abstract: Background Respectful maternity care (RMC) has been elevated in the global discourse, however, instances of disrespect and abuse remain prevalent. While several studies have highlighted promising approaches to promote RMC, this body of literature is still limited and few approaches have been scaled outside the initial study sites. Building on formative research conducted through a behavioral science lens, we sought to develop and test evidence-based, low-cost solutions to promote RMC which woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…We also understand that the level of education and cadre of the birth attendants can affect the practices of RMC, but it was not possible to obtain this information from the participants or medical record forms. Finally, high self‐reported RMC may sometimes reflect low expectations for care as has been indicated in the literature 46 . This may be the case particularly for WLHIV, who may have even lower expectations of care given their anticipated stigma.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…We also understand that the level of education and cadre of the birth attendants can affect the practices of RMC, but it was not possible to obtain this information from the participants or medical record forms. Finally, high self‐reported RMC may sometimes reflect low expectations for care as has been indicated in the literature 46 . This may be the case particularly for WLHIV, who may have even lower expectations of care given their anticipated stigma.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, high self-reported RMC may sometimes reflect low expectations for care as has been indicated in the literature. 46 This may be the case particularly for WLHIV, who may have even lower expectations of care given their anticipated stigma. A study by Smith and colleagues in Zambia reported that women's primary concern during labor and delivery was to have a healthy baby, which may lead them to minimize abusive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical techniques of verbal persuasion and modeling, drawn from the Social Cognitive Theory, were used to alter the determinants of attitude, social influence, self-efficacy, and expected outcomes (Smith et al, 2022). Similar to this, the Social Cognitive Theory's active learning and direction were used to influence the determinants' abilities and self-efficacy.…”
Section: Fig 1: the Logic Model Of The Problemmentioning
confidence: 99%
“…Most interventions in Africa focus on training providers on respectful maternity care [ 59–63 ]. Other interventions include improving the health facility environment, working with policymakers to encourage greater focus on disrespect and abuse of women, and strengthening linkages between the facility and community for accountability and governance [ 28 , 29 , 64 ]. Evidence on the effectiveness of these interventions is however limited, and there remains a dearth of interventions to improve PCMC that are grounded in theory [ 27 , 58 , 59 ].…”
Section: Introductionmentioning
confidence: 99%